2017
DOI: 10.1016/j.aap.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

An experiment on rider stability while mounting: Comparing middle-aged and elderly cyclists on pedelecs and conventional bicycles

Abstract: Pedelecs, popular among elderly cyclists, are associated with a higher injury risk than conventional bicycles. About 17% of these injuries are due to falls while (dis)mounting. Using instrumented bicycles, this study aimed to identify factors contributing to the stability of self-chosen mounting methods in four user groups: 30-45 versus 65+ years of age and males versus females. Mounting stability on pedelecs was compared with that on conventional bicycles, in controlled experimental setting (task in a fenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Recent literature suggests an increased risk while mounting or dismounting amongst EB users (Twisk et al, 2017). Our current study also showed that crashes with EBs are more often crashes while (dis)mounting (see Table 2).…”
Section: Crash Type: Mounting and Dismountingsupporting
confidence: 78%
See 3 more Smart Citations
“…Recent literature suggests an increased risk while mounting or dismounting amongst EB users (Twisk et al, 2017). Our current study also showed that crashes with EBs are more often crashes while (dis)mounting (see Table 2).…”
Section: Crash Type: Mounting and Dismountingsupporting
confidence: 78%
“…It has also been suggested that the higher mass of EBs compared to CBs may interfere with (dis)mounting (Kovácsová et al, 2016;Twisk et al, 2017). Table 2 confirms that EB users are more often involved in crashes while mounting or dismounting; 15% of EB crash victims fell while mounting or dismounting.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Future studies would benefit from the application of a similar research design to populations who may be less inclined to use active forms of transportation, such as older individuals, obese or overweight individuals, and those who may be impacted by physical injury or impairment. Previous e-bike studies with vulnerable populations have largely focused only safety [36,37]. In addition, this study could also be extended to the use of pedal-assist mountain bikes, or eMTB, on soft-surface and off-road trails.…”
Section: Discussionmentioning
confidence: 96%